The conceptions of deafness in the LIBRAS interpreters voices - Oliveira, Luciana Figueiredo de (2019)
The educational and inclusion processes of deaf subjects in regular education are often summed up in the presence of the Libras interpreter in the regular classroom. Such processes, as a rule, seem to be disregarding the singularities of the deaf subjects, leaving aside the importance of the valorization of culture and the constitution of deaf identities to the detriment of educational practices based still on the teaching of language as a ready and finished object and the subject as being passive in this process. This study aims to discuss the performance of Libras interpreters in regular education, as well as their conceptions about deaf students who accompany. This is a qualitative research, based on interviews with the Libras interpreters who work in elementary school, with data analysis performed based on the assumptions of the content analysis proposed by Bardin (2011). Probably based on inclusion policies for the deaf who privilege the linguistic aspect in detriment to the cultural and identity, the conceptions of subject and deafness presented by the Libras interpreters can still be considered reductionist. Thus, the presence of this professional in primary education, as the only or main alternative for the education of deaf subjects, has not made possible the constitution of their identity and the valorization of the deaf culture, not contributing to a critical, responsible and effective education of these subjects. It is urgent and necessary to adopt an educational model that allows the knowledge and development of relationships that, in addition to linguistic, value cultural aspects.